Potential Effect of Nutritional Fruits on Gout Therapy - A Review - Aina Amanina Abdul Jalil; Syarifah Syamimi Putri Adiba Syed Putera; Nor Safwan Hadi Nor Afendi; Ahmad Yasser Hamdi Nor Azlan; Manira Maarof (Asian Journal of Medicine & Health Sciences, 2022)
Gout is a disease caused by the deposition of monosodium urate crystal (MSU) in the tissues. The rise of uric acid over a specific threshold indicates uric acid crystal formation in gout. Pharmacological and non-pharmacological treatments have been widely developed and used to treat gout. Therefore, in this review, we discuss the current update of the potential effect of several nutritional fruits (cherry, apple, pineapple and sugar apple, respectively) on gout therapy. Thus, this review aims to outline the potential of these nutritional fruits in treating gout via in vitro, in vivo and clinical trials. A depth search was done on databases like PubMed, Google Scholar, Scopus and Web of Science to identify potentially relevant articles. The finding reveals that these fruits halt the production of the formation of uric acids due to the presence of several phytochemical constituents such as flavonoids and phenols (quercetins, catechin, epicatechin, anthocyanin, malic acids, sinapinic acids and etc), proteins, and vitamins (A, B and C). Moreover, these fruits also contain anti-inflammatory (anthocyanins, chlorogenic acid, pomolic acid, maslinic acid, bromelain, caryophyllene oxide, cyclosquamosin D and flavonoids, respectively) and antioxidant agents (polyphenols, quercetin, catechin, epicatechin, sinapinic acids, flavonoids, phenols and flavones, respectively) that are beneficial for the inflammation in gout that have been demonstrated via in vitro, in vivo, and clinical studies which were highlighted in this review. Collectively, these four potential fruits have been shown to reduce uric acids as well as inflammation, however, cherry is the one showing the highest potential in promoting healing of gout and can be developed as a promising future gout therapy.